Nominal uncertainty and inflation: the role of european union membership - Neanidis, Kyriakos C.; Savva, Christos S. (My University, 2011)
We provide evidence that higher inflation uncertainty leads to higher inflation in the new European Union (EU) member states and candidate countries only prior to EU accession. During EU accession and entry, inflation uncertainty has no effect on mean inflation
Keywords: Inflation (Finance); Inflation (Finance)--European Union countries; Inflation (Finance)--Europe; Inflation (Finance)--European Economic Community countries; Inflation (Finance); Inflation (Finance)--European Union countries; Inflation (Finance)--Europe; Inflation (Finance)--European Economic Community countries